Strategy implementation problems in small and large companies – similarities and differences in light of the research results. Lessons from the polish experience - Wołczek, Przemysław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The literature on the strategic management emphasizes the essence and importance of both the good formulation and the proper implementation of the strategy. However, business practice shows that while companies have quite highly developed skills in the area of strategy formulation, at the same time they are characterized by a surprisingly low level of skills in the scope of the effective implementation of the strategy. Various factors that affect the effectiveness of the implementation process are mentioned, including poorly developed leadership skills among management staff, the improper allocation of decision-making powers, the incompetent communication of the strategy, the lack of ability to manage changes, and the lack of appropriate motivators associated with the strategy being implemented. It is worth considering whether the companies that achieve market success are also facing such problems in the strategy implementation process. This paper is based on the results of the research conducted as part of the project entitled “The implementation of the strategy in the organization – model, determinants and implications”1. It presents five key problems faced in the strategy implementation process by small and large companies that can be considered to be effective in implementing their development concepts. It appears that the implementation of the strategy in such companies is usually hindered by two problems: “management staff overloaded with current problems” and “attention of employees focused on operational activities”. Most problems are associated with the changes occurring in the environment and the lack of appropriate motivators.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 391-421
Keywords: strategy; strategy implementation; implementation problems; small and large companies